Pediatric SARS-CoV-2 Seroprevalence in Arkansas Over the First Year of the COVID-19 Pandemic. Issue 6 (16th March 2022) - Boehme, Karl W; Kennedy, Joshua L; Snowden, Jessica; Owens, Shana M; Kouassi, Marianne; Mann, Ryan L; Paredes, Amairani; Putt, Claire; James, Laura; Jin, Jing; Du, Ruofei; Kirkpatrick, Catherine; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) seroprevalence studies largely focus on adults, but little is known about spread in children. We determined SARS-CoV-2 seroprevalence in children and adolescents from Arkansas over the first year of the coronavirus disease of 2019 (COVID-19) pandemic. Methods: We tested remnant serum samples from children ages 1-18 years who visited Arkansas hospitals or clinics for non-COVID-19-related reasons from April 2020 through April 2021 for SARS-CoV-2 antibodies. We used univariable and multivariable regression models to determine the association between seropositivity and participant characteristics. Results: Among 2357 participants, seroprevalence rose from 7.9% in April/May 2020 (95% CI, 4.9-10.9) to 25.0% in April 2021 (95% CI, 21.5-28.5). Hispanic and black children had a higher association with antibody positivity than non-Hispanic and white children, respectively, in multiple sampling periods. Conclusions: By spring 2021, most children in Arkansas were not infected with SARS-CoV-2. With the emergence of SARS-CoV-2 variants, recognition of long-term effects of COVID-19, and the lack of an authorized pediatric SARS-CoV-2 vaccine at the time, these results highlight the importance of including children in SARS-CoV-2 public health, clinical care, and research strategies.